The Role of Educated Women in Preventing Terrorism: A Feminist Theory Perspective - Bela Ardila; Ari Pitoyo Sumarno; Ahmad G. Dohamid (PT FORMOSA CENDEKIA GLOBAL, 2024)
The topic of educated women's role in terrorism prevention is increasingly relevant in security and gender studies. Educated women have great potential to contribute to terrorism prevention efforts through various social, political, and economic roles. This research aims to identify and analyze how educated women can play an effective role in preventing terrorism, as well as how feminism theory provides an in-depth perspective on their contribution. Feminism theory is used in the analysis process of this research. The results show that educated women who have quality education can significantly contribute to the prevention of terrorism through empowerment and education, deconstruction of patriarchal and militaristic narratives often used by terrorist groups, economic and social analysis, understanding the local cultural and historical context from the perspective of postcolonial feminism, and the perspective of ecological feminism.